1990
DOI: 10.1084/jem.171.1.345
|View full text |Cite
|
Sign up to set email alerts
|

An Epstein-Barr virus-specific cytotoxic T cell epitope in EBV nuclear antigen 3 (EBNA 3).

Abstract: All individuals previously infected with Epstein-Barr virus (EBV) harbor life-long a population of virus-infected B cells whose number appears to be controlled by EBVspecific, HLA-restricted (class I and class II) CTLs (CD4 and CD8) that recognize a functionally defined lymphocyte-determined membrane antigen, LYDMA (1, 2). There are two recognized types of EBV (A and B) that show sequence divergence within the reading frames encoding EBV nuclear antigens (EBNAs) 2, 3, 4, and 6 (3, 4) and differences in the mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(72 citation statements)
references
References 13 publications
(16 reference statements)
0
70
0
Order By: Relevance
“…Allele-specific motifs have been proposed for several mouse MHC types and the HLA-A2 and B27 alldes (47--49, 52). Comparison of the HLA-B8-restricted gp41 epitope 586-593 with peptides containing other HLA-B8-restricted CTL epitopes (8,9,30,53,54) reveals several potential alignments with shared characteristics at selected positions within an eight-to nine-aa region, including a hydrophobic residue (Ala, Leu, Iso, and Val) at position two, a positively charged aa at position 3, and aa with nonpolar or small polar side chains at the two COOH-terminal residues (Table 5). Definitive assignment of an HLA-B8-specific motif will require the determination of minimum effective epitopes for other HLA-BS-restricted epitopes and the use of competition experiments with variant peptides to define aa that interact with either the TCR or HLA molecule (55)(56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
“…Allele-specific motifs have been proposed for several mouse MHC types and the HLA-A2 and B27 alldes (47--49, 52). Comparison of the HLA-B8-restricted gp41 epitope 586-593 with peptides containing other HLA-B8-restricted CTL epitopes (8,9,30,53,54) reveals several potential alignments with shared characteristics at selected positions within an eight-to nine-aa region, including a hydrophobic residue (Ala, Leu, Iso, and Val) at position two, a positively charged aa at position 3, and aa with nonpolar or small polar side chains at the two COOH-terminal residues (Table 5). Definitive assignment of an HLA-B8-specific motif will require the determination of minimum effective epitopes for other HLA-BS-restricted epitopes and the use of competition experiments with variant peptides to define aa that interact with either the TCR or HLA molecule (55)(56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
“…Namely, specific killer T cells recognize the membrane antigen that is expressed on the surface of EBNApositive B cells and prevent proliferation of the virus-infected cells. Recently, transformation and recombinant vaccinia virus experiments have revealed that a significant proportion of the killer T cells recognize some members of the EBNA family such as EBNA 2, 3A, 3B, and 3C (5,8,14,25,26). Although there was no direct evidence for the recognition of these EBNA family antigens by the cytotoxic effector cells in our study, the present result may be interpreted that our PF assay reflects the degree of continuous EBNA-positive cell destruction followed by anti-EBNA antibody production in the latent stage of EBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Antigen-specific CTLs were generated from pre-expanded and fresh PBMCs stimulated with autologous mature peptide-pulsed DCs (50 g/ml for 2 h at 37°C; DC/responder ratio 1:10) in 1% ABS Ex-Vivo medium with 10 ng/ml IL7 (day 0; R&D Systems) and 20 IU/ml IL2 (starting on day 7), and harvested for analysis on day 12. The immunodominant HLA-A2-restricted NLVPMVATV peptide from the pp65 protein of CMV (CMVpp65 NLV ) 40 and HLA-B8-restricted FLRGRAYGL peptide from the latent cycle protein EBNA3A of EBV (EBV-EBNA3A FLR ) 41 were selected for this analysis. All cells were cultured at 37°C in a humidified atmosphere containing 5% CO 2 .…”
Section: Cell Cultures: Polyclonal Expansion Mixed Lymphocyte Reactimentioning
confidence: 99%